Evaluation of Project P.A.T.H.S. in Hong Kong: Utilization of Student Weekly Diary - Daniel T. L. Shek; Rachel C. F. Sun; Ching Man Lam; Daniel W. M. Lung; Sui Chung Lo (The Scientific World Journal)
Four schools participating in the experimental implementation phase of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) (Secondary 1 level) were randomly selected and invited to join this research study. After completion of the Tier 1 Program, Secondary 1 students in the participating schools were invited to write a reflective journal in the form of a weekly diary in order to reveal their perceptions and feelings regarding the Tier 1 Program and the related benefits. Results of the qualitative data analyses showed that most of the respondents (a) had positive views on the program, (b) had positive views on the instructors, and (c) stated that they had acquired competencies at societal, familial, interpersonal, and personal levels after joining the program. The present qualitative findings based on students' weekly diaries provide additional support for the effectiveness of the Tier 1 Program of P.A.T.H.S. in Hong Kong.